2019
DOI: 10.12659/msm.914485
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Classification of Os Trigonum: A Study Based on Computed Tomography Three-Dimensional Imaging

Abstract: Background The os trigonum is an accessory bone that is not fully fused with the talus during secondary ossification, and is one of the risk factors of posterior malleolus impact syndrome. The purpose of this study was to classify the os trigonum and to guide the diagnosis and treatment of related clinical diseases. Material/Methods Ankle computed tomography (CT) scans of 586 Chinese patients between October 2014 and October 2018 were reviewed. CT images of 1011 ankle j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
15
0
2
Order By: Relevance
“…However, the frequency of occurrence of the os trigonum alone was widely investigated in normal feet and it varies from 2 to 50 % (Burman & Lapidus, 1931;Mann & Owsley), and a population-specific incidence was also reported for os trigonum (Mann & Owsley; Zwiers et al). On the other hand, the frequency of the enlarged posterolateral talar tubercle (Stieda's process) is rarely reported with incidences of 35.7 % and 14.7 % in the Netherlands and Chinese population, respectively (Zwiers et al;Fu et al, 2019). The aim of this study was to provide a comprehensive understanding of the anatomical variations of the posterolateral tubercle of talus and to establish their prevalence on CT imaging.…”
Section: Introductionmentioning
confidence: 98%
“…However, the frequency of occurrence of the os trigonum alone was widely investigated in normal feet and it varies from 2 to 50 % (Burman & Lapidus, 1931;Mann & Owsley), and a population-specific incidence was also reported for os trigonum (Mann & Owsley; Zwiers et al). On the other hand, the frequency of the enlarged posterolateral talar tubercle (Stieda's process) is rarely reported with incidences of 35.7 % and 14.7 % in the Netherlands and Chinese population, respectively (Zwiers et al;Fu et al, 2019). The aim of this study was to provide a comprehensive understanding of the anatomical variations of the posterolateral tubercle of talus and to establish their prevalence on CT imaging.…”
Section: Introductionmentioning
confidence: 98%
“…The different morphological variants of os trigonum described in this study were also previously identi ed in a CT based study of a Chinese population (Fu et al, 2019). Three basic types of os trigonum based on the mode of connection were identi ed; Type 1 was a single bone that was not connected to talus, type 2 was connected to the posterior talar process by a hyaline cartilage, and type 3 was the Stieda's process.…”
Section: Discussionmentioning
confidence: 64%
“…In the study of Zwier et al, Stieda's process was found in about one-third of the patients without os trigonum (Zwiers et al, 2018). In another CT based study of a Chinese population, Stieda's process was identi ed in 14.7% of patients (Fu et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a recent CT based study, Stieda's process was found in about one-third of the patients without os trigonum (6). In another CT based study of a Chinese population, Stieda's process was identi ed in 14.7% of patients (7).…”
Section: Introductionmentioning
confidence: 92%